Student Voices in the Movement for Integration and Equity - Mode, Sophie; Michelle, Dulce (Radical Teacher, 2020)
In a time when equity and justice are at the forefront of conversations across the nation, it is essential that the voices of students are not ignored or tokenized. New York City has the most segregated public school system in the nation, more segregated now than in the 1960s. Hundreds of thousands of students spend every day in segregated classrooms, and yet our voices are not the focus. Students are powerful. Students are knowledgeable. Students are passionate. Students are the ones directly feeling the effects of an immensely segregated and inequitable system.